The Role of Problematic Smartphone Uses and Psychological Distress in the Relationship Between Sleep Quality and Disordered Eating Behaviors Among Chinese College Students - Wu, Ruipeng; Guo, Lan; Rong, Hao; Shi, Jingming; Li, Wenyan; Zhu, Minxia; He, Yongjun; Wang, Wanxin; Lu, Ciyong (Frontiers in Psychiatry, 2021)
Background: Sleep problems and eating disorders (EDs) are both serious public health concerns often seen in young adults. Yet, the underlying mechanisms for such associations are largely unknown. This study aims to examine potential serial multiple mediation effects of problematic smartphone use (PSU) and psychological distress (i.e., depressive and anxiety symptoms) in the relationship between sleep quality and disordered eating behaviors/attitudes (DEBs). Methods: A total of 4,325 students from two Tibet universities in China (2,657 females and 1,668 males) completed an online survey that included the following measurements: Eating Attitude Test-26 for disordered eating behaviors/attitudes, the Chinese Version of Pittsburgh Sleep Quality Index (CPSQI), Smartphone Addiction Scale—Short Version (SAS-SV) for problematic smartphone use, Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder-7 (GAD-7) for psychological distress. Results: While the direct path linking sleep quality and DEBs was not found to be significant (Standardized β = 0.006, 95% CI = −0.0667 0.0970), both PSU (Standardized β = 0.016, 95% CI = 0.0256 0.0591) and anxiety symptoms (Standardized β = 0.014, 95% CI = 0.0203 0.0526) may mediate a link between sleep quality and DEBs; serial multiple mediation analysis revealed that a serial indirect pathway of “sleep quality -> PSU -> anxiety symptoms -> DEBs” existed(Standardized β = 0.001, 95% CI = 0.0002 0.0012). Similarly, while the direct path linking sleep quality and DEBs was not found to be significant (Standardized β = 0.006, 95% CI = −0.0667 0.0970), both PSU (Standardized β = 0.020, 95% CI = 0.0337 0.0692) and depressive symptoms (Standardized β = 0.015, 95% CI = 0.0139 0.0652) may mediate a link between sleep quality and DEBs; serial multiple mediation analysis revealed that a serial indirect pathway of “sleep quality -> PSU -> depressive symptoms -> DEBs” existed (Standardized β = 0.001, 95% CI = 0.0006 0.0038). Conclusions: Psychological and behavioral factors may comprehensively work together, leading to flow-on effects from sleep problems to disordered eating behaviors among university students. Appropriate interventions that target problematic smartphone use could thus potentially reduce anxiety and depression levels, which in turn will provide a buffer against the negative impact of poor sleep quality on eating disorder symptoms.